Brief Overview on Over-the-Counter Medicine and their Impact on Community Health - Ahmed, Rushda; Divya, Amara; Ramyarani, Garvandha; Khair, Ummul; Das, Joyani (Journal of Pharmacy Practice and Community Medicine)
Self-care and self-medication are common practices in any health care system. The self-medication procedure includes the usage of Over-the-counter or non-prescription drugs which are obtained by individuals without a prescription from a physician for the treatment of common ailments. Lower costs, convenience, availability, and the ability to control one’s own illness are the potential benefits of over-the-counter- drugs. The risk of drug misuse, dependence, and adverse drug events is increased when the drugs are used inappropriately. Misuse and Abuse are characterized as over-consumption beyond the approved medical practice or medical norms when the hazards and unfavorable consequences outweigh the advantages. These include self-medicating at higher quantities and for longer periods of time than recommended. Improved knowledge, understanding about self-medication result in rationale use. There is an urgent need to implement legislation to promote judicious and rational use of over-the-counter drugs.
Keywords: Addiction; Drug Abuse; Self-medication; Misuse; Non-prescription drugs; Over-the-counter drugs; Regulations